HORSE AND RIDER FACTORS OF PERFORMANCE IN SHOW - JUMPING DISCIPLINE - Rudmieze, Svetlana; Fernate, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Success in each sport is made up of certain factors. Therefore, it is necessary to be acutely aware of the factors and criteria that influence performance in a particular sport. Horse riding is a very unique sport as it is a sport where two different organisms cooperate in terms of mass, size, thinking, and physical, psychological, tactical abilities and skills, as well as characteristics. It is a sport where there is practically no age limit, and where women compete alongside men. Therefore, it is difficult to find literature where several authors come to an agreement. There are often several different opinions, including on the performance-enhancing factors in the equestrian show-jumping discipline. It is quite important to evaluate the possible factors and reach a consensus in order to crystallize a possible unified system. The aim of the research is to determine the factors contributing to the performance of the rider and the horse in the show jumping discipline in different age groups. Research methods: Scientific literature review and analysis. Main results and conclusions. By theoretically researching and analysing the literature, it should be concluded that there are no concrete factors contributing to the attributed performance in the specific age stages, which can basically create uncertainty as well as consensus of opinions in future studies due to the influence of the generalization of these factors. From the context of the studied materials, it should be concluded that there is an insufficient theoretical basis, which is evidenced by a relatively narrow spectrum of topical issues. Therefore, the obtained theoretical information allows to create a basis for further practical research, thus expanding the theoretical base in the context of the current issue.